Novel multi‐component vaccine approaches for Burkholderia pseudomallei. (8th April 2019) - Morici, L.; Torres, A. G.; Titball, R. W.
Summary: Burkholderia pseudomallei is the causative agent of melioidosis. Historically believed to be a relatively rare human disease in tropical countries, a recent study estimated that, worldwide, there are approximately 165 000 human melioidosis cases per year, more than half of whom die. The bacterium is inherently resistant to many antibiotics and treatment of the disease is often protracted and ineffective. There is no licensed vaccine against melioidosis, but a vaccine is predicted to be of value if used in high‐risk populations. There has been progress over the last decade in the pursuit of an effective vaccine against melioidosis. Animal models of disease including mouse and non‐human primates have been developed, and these models show that antibody responses play a key role in protection against melioidosis. Surprisingly, although B. pseudomallei is an intracellular pathogen there is limited evidence that CD8 + T cells play a role in protection. It is evident that a multi‐component vaccine, incorporating one or more protective antigens, will probably be essential for protection because of the pathogen's sophisticated virulence mechanisms as well as strain heterogeneity. Multi‐component vaccines in development include glycoconjugates, multivalent subunit preparations, outer membrane vesicles and other nano/microparticle platforms and live‐attenuated or inactivated bacteria. A consistent finding with vaccine candidates tested in mice is the ability to induce sterilizing immunity at low challenge doses and extended time to death at higher challenge doses. Further research to identify ways of eliciting more potent immune responses might provide a path for licensing an effective vaccine. Abstract : B. pseudomallei is estimated to cause 165 000 human melioidosis cases per year, of whom more than half die. There has been progress in developing multi‐component vaccines to protect against disease, and a consistent finding is the ability to induce sterilizing immunity at low challenge doses and extended time to death at higher challenge doses. Further research to identify ways of eliciting more potent immune responses might provide a path for licensing an effective vaccine.